2015
DOI: 10.1007/s10286-015-0274-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of statins on sympathetic activity: a meta-analysis

Abstract: ObjectiveBeyond lipid-lowering properties, statins decrease sympathetic nervous activity. Due to the limited number of studies and included participants, a meta-analysis of randomized, placebo-controlled studies using microneurography (MSNA) was performed to assess sympatholytic effect of statins.MethodsWe conducted a comprehensive search of online databases (Cochrane, Embase, and EBSCO) for published human studies up to April 2014. Randomized controlled trials (parallel and crossover design) were eligible for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 31 publications
0
17
1
Order By: Relevance
“…An interesting finding of the current analysis was that the magnitude of effects of statins on improvement of LVEF was dependent on the etiology of HF; specifically, trials with a considerable number of patients with nonischemic HF had larger improvements in LVEF than did patients with ischemic etiology. The reasons for the different hemodynamic responses in ischemic and nonischemic etiologies have not been clarified but may be related to differences between the two statin types in the degree of activation of the beta‐adrenergic pathway which are unrelated to cholesterol‐lowering effects . Regardless of the factors involved, the superior treatment effect of lipophilic statins on LVEF was apparent in both ischemic and nonischemic HF compared with hydrophilic statins.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting finding of the current analysis was that the magnitude of effects of statins on improvement of LVEF was dependent on the etiology of HF; specifically, trials with a considerable number of patients with nonischemic HF had larger improvements in LVEF than did patients with ischemic etiology. The reasons for the different hemodynamic responses in ischemic and nonischemic etiologies have not been clarified but may be related to differences between the two statin types in the degree of activation of the beta‐adrenergic pathway which are unrelated to cholesterol‐lowering effects . Regardless of the factors involved, the superior treatment effect of lipophilic statins on LVEF was apparent in both ischemic and nonischemic HF compared with hydrophilic statins.…”
Section: Discussionmentioning
confidence: 99%
“…In the very early phase of MI, IS declines because of a spectrum of mechanisms that include the neurohumoral activation and acute phase of inflammatory response 3,24,25 . Although statins can quickly reduce inflammatory activity 26 and sympathetic activation 27 , its above-commented ability to inhibit prenylation seems to predominate in the modulation of IS during acute stress according to our EHC data 28 . Indeed, in in vitro model with 3T3-L1 adipocytes, statins promote downregulation of insulin-sensitive GLUT-4 and up-regulation of GLUT-1; these effects are reversed by mevalonate, demonstrating that inhibition of isoprenoid biosynthesis causes insulin resistance in adipocytes 29 .…”
Section: Discussionmentioning
confidence: 56%
“…Indeed, therapeutic doses of statins decrease Rho kinase activity in patients with atherosclerosis in an LDL-independent manner 63 . Our lab has similarly found that statin treatment improves autonomic function in experimental and clinical heart failure independent of LDL-lowering effects 6468 , and clinical studies in patients with hypertension and chronic kidney disease support the sympatholytic effect of statins in humans regardless of the presence of hyperlipidemia 6972 . Given the strong associative 7375 and experimental 76,77 data linking autonomic function and mortality in cardiovascular disease, the sympatholytic effects of statins through Rho kinase inhibition may be an important mechanism by which these drugs reduce cardiovascular risk.…”
Section: Discussionmentioning
confidence: 72%